Bilateral Numerous Warts in Upper and Lower Eyelids, in Middle-Aged Man - Mohammad Hossein Davari; Hoda Gheytasi (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Background: Warts are small, usually painless growths on the skin caused by a virus called human papillomavirus (HPV). Most, but not all, are generally harmless [1,2]. Warts can be disfiguring and embarrassing. Sometimes they itch or hurt (particularly on the feet). Some warts spread through sex. But in The eyelids are rare. Viral warts are a common skin condition, which can range in severity from a minor nuisance that resolve spontaneously to a troublesome, chronic condition [3-5]. Many different treatments are available but because warts were very large, we use a surgical procedure (excision). Purpose: To evaluate the efficacy of cut out the wart (excision) by surgery. Materials/Patients: In this case report, 56 years old man have been reported with upper and lower eyelid involvement in both eyes. Expressed warts came the age of 20 and around the eyelids of both eyes and then grows within 5 years, Sized warts at presentation were 1 to 5 mm until warts on eyelids make adverse effects on vision. Warts were also seen around the patient's neck. He had no other illnesses. The patient's mother had two warts 4 to 5 mm around her nose. We have treated the warts eye in vali Asr hospital, Birjand University of Medical Sciences. Pathologist also reported Verruca Vulgarism. Patient after surgery was visit in terms of recurrence and fortunately it was not a problem.